Analisis Rasio Pertumbuhan, Efektivitas Dan Efisiensi Anggaran Pada Kepolisian Negara Republik Indonesia (Polri) Tahun 2017 – 2022 - Abrar Prasodjo; Samsudin Samsudin; Kumba Digdowiseiso (Journal of Economic, Bussines and Accounting (COSTING), 2023)
Public organizations such as POLRI, as part of the government in Indonesia, which have a tendency to gain higher legitimacy usually have similarities with other organizations. POLRI is one of the institutions that has received a sizable APBN allocation, which has led to several opinions questioning how well its financial reports are performing. The amount of the budget received by POLRI needs to be analyzed through financial reports which are part of the Indonesia Government Financial Statements (LKPP) which have been audited by the BPK. There are several ways to calculate Financial Performance, including calculating Growth Ratios, Effectiveness Ratios, and Efficiency Ratios. The LKPP data used comes from the 2017- 2022 Fiscal Year. Data analysis uses a quantitative descriptive analysis method. The results of this study show that POLRI's financial performance uses a growth ratio in the period from the 2017 – 2022 Fiscal Year, on average experiencing a growth ratio of 3%. For the effectiveness ratio, on average it is 103.93%, which means that the National Police Budget is used very effectively, with a range of effectiveness ratio values between 91.2% (2021 Fiscal Year, effective) and 113.9% (2019 Fiscal Year, very effective). Meanwhile, from the efficiency ratio, the performance status of the Polri budget during the 2017 – 2022 period was 74.78% (Efficient), with a range of values between 60% - 80%. Keywords: Growth Ratio, Effectiveness Ratio, Efficiency Ratio